In vitro Antibiotic Susceptibility Patterns of Ornithobacterium rhinotracheale from Commercial Chickens in Argentina# - Churria , Carlos D. Gornatti; Loukopoulos, Panayiotis; Vigo, German B.; Sansalone, Pablo; Machuca, Mariana A.; Nievas, Victorio; Piscopo, Miguel; Loyola, Miguel Herrero; Petruccelli, Miguel A. (International Journal of Poultry Science, 2016)
Ornithobacterium rhinotracheale is a bacterial pathogen of the poultry industry causing severe economic losses worldwide. Fifteen β-hemolytic and 23 non-hemolytic O. rhinotracheale isolates from commercial broiler and broiler breeder chicken flocks were obtained and their sensitivity to ampicillin, trimethoprim-sulfamethoxazole, gentamicin, enrofloxacin, erythromycin, florfenicol, doxycycline and fosfomycin tested by a disk diffusion method. All isolates were non-susceptible to gentamicin. Most were non-susceptible to enrofloxacin, erythromycin, trimethoprim-sulfamethoxazole, doxycycline and fosfomycin, while most were susceptible to ampicillin and florfenicol. Susceptibility to ampicillin and florfenicol was significantly higher compared to all other antibiotics tested. Overall, 34 out of 38 (89.5%) isolates were found to be multiresistant. The presence of these multiresistant O. rhinotracheale isolates is suggestive of antibiotic over and misusing in the local poultry industry. To the authors’ knowledge, this is the first work in South America reporting in vitro antibiotic susceptibility patterns of Argentine β-hemolytic and non-hemolytic O. rhinotracheale isolates.